Embracing hobbies: unleashing the magic of well-being / Syazliana Kasim, Farrah Othman and Noor Azillah Mohamad Ali - Kasim, Syazliana; Othman, Farrah; Mohamad Ali, Noor Azillah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In the whirlwind of modern life, we often find ourselves caught up in the hustle and bustle of work, chores, and responsibilities, leaving little room for moments of joy and self-discovery. Yet, in the simple act of nurturing a hobby, lies the key to unlocking a treasure trove of well-being and happiness. Hobbies are like magic potions that infuse our lives with a sense of purpose, fulfillment, and balance, creating an overall sense of good being among people.